2005
DOI: 10.1002/marc.200500678
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multiblock Polymer Containing Narrow Polydispersity Blocks

Abstract: Summary: We have developed a new strategy to prepare multiblock polymers and copolymers via one‐ or two‐step polymerization using a polymerizable cyclic trithiocarbonate (CTTC), 4,7‐diphenyl‐[1,3]dithiepane‐2‐thione. CTTC undergoes ring‐opening process to incorporate a trithiocarbonate moiety. The trithiocarbonate moiety in turn, functions as a reversible addition fragmentation chain transfer (RAFT) agent. Through this mechanism, multiblock polystyrenes and polystyrene‐block‐ poly(butyl acrylate) copolymers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 27 publications
0
42
1
3
Order By: Relevance
“…For this reason, a number of cyclic thiocarbonylthio compounds including 5-and 6-membered CTTCs were synthesized and evaluated as chain-transfer agents by our group. [6] However, our preliminary outcomes contrasted with the results reported by Hong et al [4,5] using 7-membered CTTCs. Indeed, we found that 5-and 6-membered CTTCs were inactive vis-à -vis propagating polystyryl or polybutylacrylyl radicals.…”
Section: Introductioncontrasting
confidence: 57%
See 1 more Smart Citation
“…For this reason, a number of cyclic thiocarbonylthio compounds including 5-and 6-membered CTTCs were synthesized and evaluated as chain-transfer agents by our group. [6] However, our preliminary outcomes contrasted with the results reported by Hong et al [4,5] using 7-membered CTTCs. Indeed, we found that 5-and 6-membered CTTCs were inactive vis-à -vis propagating polystyryl or polybutylacrylyl radicals.…”
Section: Introductioncontrasting
confidence: 57%
“…[3] Recently, Hong et al [4] reported the use of cyclic trithiocarbonates (CTTCs) as a new type of mediating agent in the radical polymerization of styrene and butyl acrylate. [5] The mechanism proposed for these cyclic agents is similar to the original RAFT mechanism for conventional trithiocarbonates, except that the fragmentation step is a ringopening reaction. Therefore, the reinitiating P n -R radical is composed of a P n tail bonded to thiocarbonylthio moieties (Scheme 1b, where Z ¼ SR').…”
Section: Introductionmentioning
confidence: 99%
“…[197,211] One method of synthesizing these involves a ring opening RAFT polymerization making use of the cyclic trithiocarbonate 106 (Scheme 16). [211] Multiblock copolymers have also been prepared from the multi-dithiocarbamate 107. [126] …”
Section: Block Copolymersmentioning
confidence: 99%
“…In addition, RAFT polymerization with polytrithiocarbonates has already been used to prepare segmented copolymers composed of poly(N,N-dimethylacrylamide) (DMA) and poly(N-isopropylacrylamide) (NIPAM) [31], of polystyrene and poly(4-tert-butylstyrene) [32] and of a random DMA-NIPAM copolymer and poly(4-vinylpyridine) [33]. It has been shown that this strategy can also be carried out preparing the polytrithiocarbonates in situ by employing cyclic trithiocarbonates in the first polymerization [34,35]. It goes without saying that in principle also RAFT agents with other chemical groups (e.g., difunctional dithiocarbamates [36]) can be utilized.…”
Section: Introductionmentioning
confidence: 99%